2021
DOI: 10.3390/cells10092180
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Regulation of SnRK2 Kinases

Abstract: SNF1-related kinases 2 (SnRK2s) are central regulators of plant responses to environmental cues simultaneously playing a pivotal role in the plant development and growth in favorable conditions. They are activated in response to osmotic stress and some of them also to abscisic acid (ABA), the latter being key in ABA signaling. The SnRK2s can be viewed as molecular switches between growth and stress response; therefore, their activity is tightly regulated; needed only for a short time to trigger the response, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 143 publications
0
30
0
Order By: Relevance
“…Moreover, we have found that SAPK7 can bind to CRP and phosphorylate it at S162 and S165 to promote CWMV infection in plant. Interestingly, SAPK7 is a member of the plant SnRK2 protein kinase family which are mostly involved in plant responses to abiotic environmental stresses [ 44 ]. Geminiviruses interact with multiple plant protein kinases, such as SnRK1, to modulate host signaling networks prompting viral infection [ 11 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have found that SAPK7 can bind to CRP and phosphorylate it at S162 and S165 to promote CWMV infection in plant. Interestingly, SAPK7 is a member of the plant SnRK2 protein kinase family which are mostly involved in plant responses to abiotic environmental stresses [ 44 ]. Geminiviruses interact with multiple plant protein kinases, such as SnRK1, to modulate host signaling networks prompting viral infection [ 11 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…SnRK2‐I, SnRK2‐II and SnRK2‐III modulate plant growth and abiotic stress responses, in particular, responses to drought‐ and salt‐triggered osmotic stress (Zhang et al ., 2011; Fujii & Zhu, 2012; Fujita et al ., 2013; Lin et al ., 2020). Compared to SnRK2‐II and SnRK2‐III, little is known about the function, substrates and regulatory mechanisms of SnRK2‐I in higher plants (Maszkowska et al ., 2021). SnRK2‐I is involved in responses to salt and osmotic stress by phosphorylating VARICOSE (VCS) and EARLY RESPONSE TO DEHYDRATION (ERD); however, its response to ABA was unknown (Fujii et al ., 2011; Krzywińska et al ., 2016; Lin et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on identifying the SnRK2‐I substrates associated with fruit quality and clarifying the underlying role of SnRK2‐I in osmoregulation and ripening. This information could help to identify candidate genes/phosphorylation sites and thereby improve our understanding of the balance between stress responses and fruit quality (Zhang et al ., 2011; Lin et al ., 2020; Maszkowska et al ., 2021). FaSnRK2.6, a member of the SnRK2‐III family, is a negative regulator of strawberry fruit ripening and anthocyanin accumulation (Han et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, SnRK2s are plant-specific Ser/Thr protein kinases, either auto-phosphorylated or trans-phosphorylated by other kinases when ABA receptors specifically sequester PP2Cs, thereby facilitating SnRK2s activation. The active SnRK2s by their well-conserved kinase catalytic domain positively regulate downstream ABA-responsive genes via the phosphorylation of TFs, which include bZIP transcription factors like ABRE (ABA-responsive element)-binding (AREB) proteins or ABRE-binding factors (ABFs) [45][46][47]. SnRK2s mediated AREB/ABFs phosphorylation is a crucial ABA-dependent regulation.…”
Section: Introductionmentioning
confidence: 99%